Antiangiogenic properties of nanoparticles: a systematic review - Saeed BA (Dove Medical Press, 2019)
Brhaish Ali Saeed,1 Vuanghao Lim,1 Nor Adlin Yusof,1 Kang Zi Khor,1 Heshu Sulaiman Rahman2,3, Nozlena Abdul Samad1  1Integrative Medicine Cluster, Advanced Medical and Dental Institute, SAINS@ Bertam, Universiti Sains Malaysia, Kepala Batas 13200, Pulau Pinang, Malaysia; 2Department of Clinic and Internal Medicine, College of Veterinary Medicine, University of Sulaimani, Sulaymaniyah City 46001, Republic of Iraq; 3Department of Medical Laboratory Sciences, College of Health Sciences, Komar University of Science and Technology, Sarchinar District, Republic of IraqAbstract: Nanoparticles appear to be one of the most promising agents that offer efficacy in angiogenesis-related disease therapy. The objective of this research is to systematically review studies that have probed into the effect of nanoparticles on angiogenesis. Selected inclusion criteria were used to extract articles, references that were cited in the initial search were sought to identify more potential articles, and articles that did not meet the inclusion criteria and duplicates were discarded. The spherical shape was shown to be the most common shape employed to investigate the role of nanoparticles in angiogenesis therapy. The size of nanoparticles appears to play a crucial role for efficacy on angiogenesis, in which 20 nm emerged as the preferred size. Gold nanoparticles exhibit the most promise as an antiangiogenesis agent, and the toxicity was adjustable based on the dosages applied.Keywords: nanoparticles, angiogenesis, antiangiogenesis, size, shape, toxicity